2021
DOI: 10.1038/s41419-021-03940-0
|View full text |Cite
|
Sign up to set email alerts
|

Operative ubiquitin-specific protease 22 deubiquitination confers a more invasive phenotype to cholangiocarcinoma

Abstract: Oncogenic ubiquitin-specific protease 22 (USP22) is implicated in a variety of tumours; however, evidence of its role and underlying molecular mechanisms in cholangiocarcinoma (CCA) development remains unknown. We collected paired tumour and adjacent non-tumour tissues from 57 intrahepatic CCA (iCCA) patients and evaluated levels of the USP22 gene and protein by qPCR and immunohistochemistry. Both the mRNA and protein were significantly upregulated, correlated with the malignant invasion and worse OS of iCCA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Our study found that USP22 might act upstream of p-AKT(S473), however with or without serum incubation USP22 still upregulates PPARγ expression. Therefore USP22 stabilizes PPARγ may independently from AKT activation, and this implies that USP22 involves multiple regulation pathways 45 . Importantly, previous study has clarified that AKT pathway is significantly activated in HCC patients 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that USP22 might act upstream of p-AKT(S473), however with or without serum incubation USP22 still upregulates PPARγ expression. Therefore USP22 stabilizes PPARγ may independently from AKT activation, and this implies that USP22 involves multiple regulation pathways 45 . Importantly, previous study has clarified that AKT pathway is significantly activated in HCC patients 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer (PCa), known for its high malignancy, poses formidable challenges in treatment and prognosis, primarily due to its propensity for aggressive invasion and metastasis [1]. Clinically, many patients with PCa, are often accompanied by elevated levels of alkaline phosphatase and circulating bilirubin [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miR-125a, belonging to the miR-10 family, has been shown to foster resistance to gemcitabine in PCa cells by targeting A20 [14]. miR-125a belongs to the miR-10 family, which includes two homologs (hsa-miR-125b-1, Am J Cancer Res 2024;14 (1):114-129 hsa-miR-125b-2) that play key roles in various molecular and cellular processes, such as differentiation, proliferation, apoptosis, and regulation of matrix metalloproteinases [15]. let-7 was first identified in 2000 and is the second miRNA identified after lin-4, which has 13 family members with the same sequence homology in the seed region, most of which are associated with the regulation of cancer drug sensitivity [16].…”
Section: Introductionmentioning
confidence: 99%